2018
DOI: 10.1159/000494365
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Digital Medicine Testing: A NODE.Health Perspective Intended to Help Emerging Technology Companies and Healthcare Systems Navigate the Trial and Testing Period prior to Full-Scale Adoption

Abstract: Over the last several years, there has been rapid growth of digital technologies attempting to transform healthcare. Unique features of digital medicine technology lead to both challenges and opportunities for testing and validation. Yet little guidance exists to help a health system decide whether to undertake a pilot test of new technology, move right to full-scale adoption or start somewhere in between. To navigate this complexity, this paper proposes an algorithm to help choose the best path toward validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A previous study showed that CM-SHARE, a voluntary-use digital health solution, was successfully integrated into a real-world primary care setting with high adoption and consistent use in caring for patients with cardiometabolic conditions [ 12 ]. In this study, following principles of the digital health technology development and deployment [ 23 , 24 ], we first tested CM-SHARE among a small group of pilot users (ie, PCPs) before spreading to a much broader group of PCP end users. Although there is an increasing availability of digital tools created by health care or high-technology companies, little is known about whether the impact of these digital tools on pilot users is sustained when the technology is spread to a much broader group of users [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that CM-SHARE, a voluntary-use digital health solution, was successfully integrated into a real-world primary care setting with high adoption and consistent use in caring for patients with cardiometabolic conditions [ 12 ]. In this study, following principles of the digital health technology development and deployment [ 23 , 24 ], we first tested CM-SHARE among a small group of pilot users (ie, PCPs) before spreading to a much broader group of PCP end users. Although there is an increasing availability of digital tools created by health care or high-technology companies, little is known about whether the impact of these digital tools on pilot users is sustained when the technology is spread to a much broader group of users [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%